2007
DOI: 10.1111/j.1524-475x.2007.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

How heel oxygenation changes under pressure

Abstract: The mechanism of heel pressure ulcers after hip surgery is not entirely understood. The purpose of this one-group, prospective, repeated-measures design study was to examine how the external pressure of the bed surface affects heel skin oxygen tension in adults on the first 3 days after hip surgery. Transcutaneous oxygen sensors were placed on the plantar surface of each foot, close to the heels. Measures were taken on room air and with an oxygen challenge with the heels (1) suspended above the bed surface (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Fluorescence imaging using ICG alone does not provide this information but when combined with magnetic resonance lymphography, there may be a basis for more accurate estimate of transient lymph packet size and volume [14] . Much research supports the view that dermal capillaries can collapse under clinically relevant magnitudes of uniaxial pressure (between 40 and 80 mmHg), leading to partial or total localised ischaemia [15,16] . The present study has shown that similar pressures can elicit changes in lymphatic function which might contribute to the cascade of mechanically-induced tissue damage, commonly leading to pressure ulcers.…”
Section: Discussionmentioning
confidence: 98%
“…Fluorescence imaging using ICG alone does not provide this information but when combined with magnetic resonance lymphography, there may be a basis for more accurate estimate of transient lymph packet size and volume [14] . Much research supports the view that dermal capillaries can collapse under clinically relevant magnitudes of uniaxial pressure (between 40 and 80 mmHg), leading to partial or total localised ischaemia [15,16] . The present study has shown that similar pressures can elicit changes in lymphatic function which might contribute to the cascade of mechanically-induced tissue damage, commonly leading to pressure ulcers.…”
Section: Discussionmentioning
confidence: 98%
“…A substantial volume of evidence supports the view that dermal capillaries may collapse under clinically relevant magnitudes of uniaxial loading, leading to partial or total localised ischaemia [2,5,24]. By comparison, collapse of dermal lymphatic vessels under equivalent loading has only been demonstrated by two seminal studies by Miller and Seale [10,11], using the canine hind limb.…”
Section: Introductionmentioning
confidence: 84%
“…13 Simultaneous changes in tcO 2 and skin temperature have been recorded during the period of reactive hyperemia. 8,14 A blunted hyperemic response is related to subsequent PU development in patients undergoing lengthy surgeries 15 and this response has also been observed in persons with diabetes mellitus and persons undergoing amputation. 16 Studies have shown that various turning schedules on special pressure-relieving bed surfaces reduce the incidence of PU.…”
Section: ■ Introductionmentioning
confidence: 91%
“…7,8 Decreased levels of tcO 2 are seen with increasing external loading pressure 9 and in areas over bony prominences such as the trochanters, 10 sacrum, 11 and heels. 8 Skin temperature fluctuates in response to pressure application 12 and may indicate changes in skin blood flow.…”
Section: ■ Introductionmentioning
confidence: 97%